Enhancing Local Designers Skill in Rattan Furniture Industries in Cirebon through Comprehensive-Design Approach Regarding Buyers’ Dependencies Prevention - Andar Bagus Sriwarno (Journal of Visual Art and Design, 2009)
Between the 1970s and the 1990s, the Indonesian economy has been transforming from an agriculture-based to an industry-based economy. According to this condition, Cirebon growth rapidly to export rattan goods even this city has no resources in rattan. The lack of design quality, export regulation and global economic crisis become the main factor to affect the decrease of company’s income at recent. Despite the crisis, government is now trying to recover by inviting design expert to improve design skills and capacity building of entrepreneurs in particular small-medium scale enterprises. This study aims to define why Cirebon still lags behind in industrial competitiveness regarding rattan furniture design. The intervention program of design is conducted to seek out the craftsman’s ability and determined the kind of design competitiveness advantages according their nature of business.